A Portable Piezoelectric Tactile Terminal for Braille Readers - Ramiro Velázquez; Hermes Hernández; Enrique Preza (Applied Bionics and Biomechanics)
This paper introduces a novel concept on reading assistive technologies for the blind: the TactoBook, a system that is able to translate entire electronic books (eBooks) to Braille code and to reproduce them in portable electronic Braille terminals. The TactoBook consists of a computer-based translator that converts fast and automatically any eBook into Braille. The Braille version of the eBook is then encrypted as a file and stored in a USB memory drive which is later inserted and reproduced in a compact, lightweight, and highly-portable tactile terminal. In particular, this paper presents a piezoelectric ultrasonic actuation approach to design and implement such portable Braille terminal. Actuating mechanism, design concept, first prototype, and performance results are presented and discussed.